Prevalence and Antimicrobial Resistance Pattern of Pseudomonas Aeruginosa Isolated from Different Clinical Samples at Tertiary Care Hospital in Nepal - Sah, Rinku; Shah, Pratima; Sharma, Abhilasha; Baral, Ratna; Khanal, Basudha; Bhattarai, Narayan (Medical Journal of Eastern Nepal, 2023)
Background: Pseudomonas aeruginosa is one of the commonest organism causing different infections like wound infections, Lower Respiratory Tract Infection, Urinary tract infection, infections in burn patient in hospital setting. The increasing trend of antibiotic resistance in Pseudomonas aeruginosa poses a challenge to their empiric treatment with conventional agents. So, the objective of this study was to determine the prevalence and antimicrobial resistance pattern of Pseudomonas aeruginosa isolated from different clinical samples.Methods: This was descriptive cross-sectional study carried out in the Microbiology laboratory, BPKIHS from March–August 2022. Identification of Pseudomonas aeruginosa was done by standard protocol and antimicrobial susceptibility testing was done by Kirby-Bauer disc diffusion method following Clinical Laboratory Standard Institute guidelinesResults: A total of 16,950 clinical samples were processed of which 198 isolates of Pseudomonas aeruginosa were isolated mainly from urine, pus, blood, sputum, wound swab, BAL (broncho-alveolar lavage). Of  the total Pseudomonas aeruginosa isolated 78.3% were resistant to ceftazidime, 71.2% were resistant to cefepime, 62.1% were resistant to ceftriaxone followed by Piperacillin 59%, ciprofloxacin 43.4%, levofloxacin 39.3%, Gentamicin 36.3%, Imipenem 31.3%. None of the isolates were resistant to colistin. This study shows that the organism was highly sensitive to Amikacin (76.7%), Tobramycin (74.7%) and Piperacillin+tazobactam (PIT-71.7%) which could be the good choice for the treatment of this organism.Conclusion: Periodic antimicrobial surveillance is essential to update the data for the prevalence and changing susceptibility pattern of the antibiotics over the period of time as this will help in choosing appropriate antibiotics for the treatment.